2005
DOI: 10.4049/jimmunol.174.3.1348
|View full text |Cite
|
Sign up to set email alerts
|

The CD200 Receptor Is a Novel and Potent Regulator of Murine and Human Mast Cell Function

Abstract: CD200R is a member of the Ig supergene family that is primarily expressed on myeloid cells. Recent in vivo studies have suggested that CD200R is an inhibitory receptor capable of regulating the activation threshold of inflammatory immune responses. Here we provide definitive evidence that CD200R is expressed on mouse and human mast cells and that engagement of CD200R by agonist Abs or ligand results in a potent inhibition of mast cell degranulation and cytokine secretion responses. CD200R-mediated inhibition o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
100
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(105 citation statements)
references
References 53 publications
4
100
1
Order By: Relevance
“…3 A, B, available at www.jneurosci.org as supplemental material). Previous studies have shown that CD200 engagement with its receptor downregulates inflammation; thus, administration of a CD200 fusion protein ameliorated changes observed in collagen-induced arthritis (Gorczynski et al, 2002), and CD200 -CD200R interaction has also been reported to prevent degranulation and cytokine release from mast cells (Cherwinski et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…3 A, B, available at www.jneurosci.org as supplemental material). Previous studies have shown that CD200 engagement with its receptor downregulates inflammation; thus, administration of a CD200 fusion protein ameliorated changes observed in collagen-induced arthritis (Gorczynski et al, 2002), and CD200 -CD200R interaction has also been reported to prevent degranulation and cytokine release from mast cells (Cherwinski et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…In vitro studies have shown that ligation of CD200R results in decreased degranulation and cytokine secretion by mast cells, monocytes and macrophages (Jenmalm et al, 2006;Cherwinski et al, 2005). In addition, deletion of the CD200 gene in mice results in enhanced susceptibility to auto-immune disease and increased myeloid response to inflammation .…”
Section: E-mail Address: Lmeyaard@umcutrechtnl (L Meyaard)mentioning
confidence: 99%
“…14,15 If we attempt to reconstitute and de-activate macrophage function (by direct ligation of CD200R with anti-CD200R monoclonal antibodies or by a CD200Fc), attenuation of retinal or CNS inflammation can be achieved 14,16 as well as regulation of other myeloid cells, including mast cells in the lung. [17][18][19][20] How do we keep the peace? A premise lies that there is continual immunosurveillance, akin to CNS, and that alongside the immune cell inhabitants of the retina and choroid, together achieve constant sensing to respond to danger signals.…”
Section: Keeping the Peacementioning
confidence: 99%